(untitled) (Revista Nacional de Odontología, 2015)
Introduction: some studies have strictly treated the association between the most frequent oral pathologies and the social economic and educational levels, finding out that the lower the social economic and educative level, the higher the presence of oral pathologies. The goal of this study was to describe the social demographic variables, oral health habits, experience and prevalence of tooth decay of the trainees of sena oral health technical program, in Medellín, Colombia. Materials and methods: descriptive cross sectional study in 90 trainees from 15 to 40 years of age. Two dental surgeons were previously calibrated, students were evaluated, and the experiences and prevalence proportions on tooth decay were calculated by the cop-d Index, recommended by the who. The description of the variables was made, the association between the dependent variable and the social demographic variables was observed, as well as oral hygiene habits and access to health services. Results: 65.6% (59 trainees) belonged to a low social class. 61.1% (55 trainees) were affiliated to the subsidized health system. Prevalence of tooth decay was 30%, experience was 67.7%. There was a significant statistic association between “What elements do you use to brush your teeth?” with the dependent variable (p = 0.037). Conclusions: in general the population’s oral health was good, which coincides with the progressive decrease of prevalence of tooth decay showed in the third and fourth national study on oral health, in the same age range.